IMPLEMENTASI PEMERIKSAAN PSIKOLOGIS ANAK BERKEBUTUHAN KHUSUS DI SD KABUPATEN MOJOKERTO - Satiningsih Satiningsih; Ira Darmawanti; Riza Noviana Khoirunnisa; Pinkan Pinardi; Raviika Widyasari Wowor (Program Studi S1, S2, S3 Mananajemen Pendidikan Universitas Negeri Surabaya, 2023)
The process of psychological assessment is a method used to evaluate the cognitive, emotional, and behavior-related aspects of children who have special needs. Within the framework of SD (primary schools) in Mojokerto regency, an assessment was carried out to determine the form of special needs and the condition of children's development aspects with indications of learning obstacles after the pandemic era. The assessments carried out include observation, interviews and standardized tests, and input from several professionals, including teachers, psychologists and special education specialists. The results showed a process of learning decline due to the lack of stimulation and interaction with indications of slow learner students and attention hyperactivity disorder (ADHD). As a follow-up to a series of community service activities, school staff received socialization and individual learning planning.